Urinary metabolomics reveals myo-inositol and (E)-Monocrotophos associate with prognosis in ACS comorbid with T2DM and preserved renal function - Mingyu Duan; Zhihan Zhang; Ruhua He; Yameng Zhang; Xueying Zhang; Miradil Dilshat; Jun He (Scientific Reports)
Abstract Type 2 diabetes mellitus (T2DM) is closely associated with an increased risk and adverse event of acute coronary syndrome (ACS). The present study aims to investigate the association between differential urinary metabolites and major adverse cardiovascular events (MACEs) in patients with ACS co-morbid T2DM with preserved renal function, and to explore the potential value of the metabolites as prognostic biomarkers in this population. Ultra-high performance liquid chromatography-mass spectrometry (UHPLC/MS) was used to analyze urine samples from ACS co-morbid T2DM. Spearman’s correlation was used to examine the association between differential metabolites and serum fasting blood glucose (FBG), glycated hemoglobin (HbA1c), Syntax score I, and MACE. The Cox proportional hazards models and Kaplan–Meier survival curves were used to identify MACE risk factors. A total of 101 differential urinary metabolites were identified, of which seven showed a correlation with FBG, HbA1c, Syntax score I and MACE. In particular, myo-inositol and (E)-Monocrotophos emerged as significant indicators of poor prognosis in ACS co-morbid with T2DM. Urinary metabolomic alteration is closely associated with clinical manifestation of ACS co-morbid T2DM. Urinary myo-inositol and (E)-Monocrotophos may be considered as prognostic biomarkers of ACS co-morbid T2DM.